Students' Metacognitive Awareness and Reading Comprehension of Narrative Texts - Rosnaeni Rosnaeni; Muhammad Zuhri Dj; Hasriati Nur (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2020)
ABSTRACTThis study aims to describe the relationship of students' metacognitive awareness and their reading comprehension of narrative texts by employing a correlational study design. The participants of this study were students of IPS 3 Class of SMAN 3 Bone, South Sulawesi, consisting of 25 students. They were selected as participants for this study using cluster sampling. The researchers used a questionnaire and test to collect the data from participants. The questionnaire was used to determine the students' metacognitive awareness, while the test was used to assess their reading comprehension of narrative texts. Pearson Product Moment and regression analyses were conducted to find out the correlation between the two variables. Results of this study show a significant correlation between metacognitive awareness and students' reading comprehension of narrative texts with r 0.786 > r table 3.961. This research could have implications for the English teacher, students, and next researchers. ABSTRAKTujuan dari penelitian ini adalah untuk mendeskripsikan hubungan antara kesadaran metakognitif siswa dengan pemahaman bacaan mereka dalam teks naratif. Penelitian korelasional digunakan dalam penelitian ini. Sampel penelitian ini adalah siswa kelas XI IPS 3 SMAN 3 Bone. Mereka dipilih dengan menggunakan cluster random sampling yang terdiri dari 25 siswa. Peneliti menggunakan angket dan tes untuk mengumpulkan data dari sampel. Angket digunakan untuk mengetahui metakognitif siswa dan tes digunakan untuk mengetahui pemahaman bacaan siswa dalam teks naratif. Product Moment Pearson dan analisis regresi digunakan untuk mengetahui korelasi antara dua variabel. Hasil penelitian menunjukkan bahwa terdapat hubungan yang signifikan antara kesadaran metakognitif dengan kemampuan membaca siswa dalam teks naratif dengan r 0,786> r tabel 3,961. Penelitian ini dapat berimplikasi pada guru bahasa Inggris, siswa, dan peneliti selanjutnya. How to Cite: Rosnaeni, Dj. M. Zuhri , Nur, H. (2020). Students' Metacognitive Awareness and Reading Comprehension of Narrative Texts. IJEE (Indonesian Journal of English Education), 7(1), 72-84. doi:10.15408/ijee.v7i1. 17027